Cell Fusion Overviews and Methods - Pfannkuche, Kurt.; Pfannkuche, Kurt. (Methods in Molecular Biology,, 2015)
This volume details protocols on detection and analysis of fusion events in various cell types in vitro and in vivo. Additional, protocols aim to facilitate the future highly relevant process of engineering cells for specific purposes, such as generation of transgenic embryos and development of hybrid cells, in order to tackle specific tasks in cell biology and medicine. Written for the Methods in Molecular Biology series, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Practical and authoritative, Cell Fusion: Overviews and Methods, Second Edition serves as an ideal reference on cell fusion and laboratory protocols.